Do transgender men have equal access to health care and engagement in preventive health behaviors compared to cisgender adults?. (9th August 2018) - Seelman, Kristie L.; Miller, Jordan F.; Fawcett, Zoe E. R.; Cline, Logan
ABSTRACT: Using 2015 Behavioral Risk Factor Surveillance System data, this study investigates whether transgender men have equal access to health care and engagement in preventive health behaviors compared to cisgender adults in the U.S. and whether race/ethnicity, socioeconomic status, and rural residence moderate these relationships. Once controlling for sociodemographic factors, we do not find differences for transgender men. Rural transgender men were less likely to have a personal doctor or receive a blood cholesterol screening than their urban peers; transgender men with less education were more likely to have a cholesterol screening. We detail implications for social workers within health care.